Evaluation of three immunological tests for the diagnosis of pulmonary tuberculosis in a rural endemic area of Bangladesh - Islam, Mohammad Tariqul; Rabbi, Fazle; Ferdous, Shameema; Parvin, Ummey Shahnaz; Hossain, Akram; Hossain, Mohammad Sorowar (© 2014 Elsevier Ltd, 2016)
This article was published in the International Journal of Mycobacteriology [ © 2014 Elsevier Ltd. ] and the definite version is available at :http://dx.doi.org/10.1016/j.ijmyco.2014.03.003 The Journal's website is at: http://linkinghub.elsevier.com/retrieve/pii/S2212553114000284